Effect of Liquid Media Formulations in the Growth of Biological Agents Derived from Trichoderma sp. and Gliocladium sp. and Their Potential in Controlling Alternaria sp. Leaf Spot on Apple - Unun - Triasih (Gontor AGROTECH Science Journal, 2021)
Several types of antagonistic fungi that are used as biological agents to control plant diseases include Trichoderma sp. and Gliocladium sp. But in its growth, it requires alternative media that are easy and cheap to obtain, one of which is the use of rice washing water and coconut water. The purpose of this study was to determine the potential of liquid media for washing rice water and coconut water on the growth of Trichoderma sp. and Gliocladium sp. The test results showed that the conidia density of the fungus Trichoderma sp. Ranged from 2,53 to 9,19 times that of the control, Gliocladium sp. 1,35 – 3,73 times as much. The pH of acidic media can produce the highest wet weight and dry weight  at P5, namely Trichoderma sp. 10.67 grams of wet weight and 0,26 grams at pH 5,01. Gliocladium sp. Has the highest wet weight at P5, namely 24,25 grams and 2,73 grams dry weight. Antagonist test against Alternaria sp. best to use Trichoderma sp. 79,39%. The conclusion of this test is the fungus Trichoderma sp. and Gliocladium sp. can grow in all media compositions except in P0 treatment (control) because mycelia cannot grow in sterile water and has the ability to inhibit the growth of Alternaria sp.